EFFECT OF PERIODIC FASTING ON GROWTH AND FEED EFFICIENCY IN GIANT FRESHWATER PRAWN (MACROBRACHIUM ROSENBERGII, DE MAN 1879) - Utomo, Waskito Dwi; Hakim, Riza Rahman; Sutarjo, Ganjar Adhywirawan (xxxx-xxxx)
There are obstacles in the aquaculture business that is still often faced by farmers, one of the challenges is the high price of commercial feed. Feed as an energy source for growth is a reasonably high-cost component in production that reaches 40-89 %. In the control of food for efficiency, it could be done by the fasting method. This research was aimed to analyze the effect of periodic fasted of giant prawn (Macrobrachium rosenbergii de Man, 1879) against growth and feed efficiency. This research was conducted at IBAP Installation, Probolinggo District - East Java Province. The experimental method used completely randomized design with five treatments and three replications, such as; P0: feeding without fasting (as control), P1: a-day fasted, a-day feeding, P2: a-day fasted, two-days feeding, P3: a-day fasted, three-day feeding, P4: a-day fasted, four-days feeding, P5: a-day fasted, five-day feeding. The results showed that periodic fasted of M. rosenbergii no significant effect on the daily growth rate, absolute weight growth, and feed efficiency. However, by looking at the rate of growth, this fasting method could be used as an alternative to saving feed. The P5 showed the most effective in increasing daily growth rate, absolute weight growth, and effectiveness of giant prawn feeding. The strategy of periodic fasted to increase the production of giant prawns should consider the other supporting factors such as ideal water quality (pH, temperature, and DO), proper stocking density, and feeding periods on schedule.